Effects of "Owned By" versus "Made In" for Willingness to Buy Australian Brands - Cheah, Isaac; Phau, Ian (Emerald Group Publishing Limited, 2015)
Purpose – This paper aims to examine the effects of economic nationalism and consumer ethnocentrism in the form of country of origin (COO) cues specifically “Made in…” and “Owned by…” on the product judgment of bi-national wine brands (brands with multiple country affiliations). Further, the role of consumer product knowledge is examined as a moderator of these xenophobia attitudes. Design/methodology/approach – A self-administered questionnaire was designed using established scales. A convenience sample was drawn from participants attending a major wine trade exhibition in Western Australia and university students. A variety of statistical techniques were used to analyse the data. Findings – High levels of economic nationalism and anti-foreign sentiment was so strong that respondents did not want products that had any association with a foreign country, regardless of whether the products are directly or indirectly related to a foreign origin. This suggests that Australian consumers are not any more receptive to bi-national brands; as such domestic affiliations have not diluted the economic nationalistic sentiment. Further, results confirm that Australian consumers use COO cues as part of wine evaluations. Consumers with low product knowledge are likely to rely on extrinsic country cues to reinforce their brand evaluation, whereas consumers who are more knowledgeable are found to base evaluations on intrinsic attributes rather than extrinsic cues. Research limitations/implications – Only respondents from Perth, Western Australia were chosen, thus limiting the representativeness of the sample. Other cultural contexts and product categories based on a larger sample size should be investigated in the future. Practical implications – This research provides useful consumer insights and new market entry implications in terms of advertising and branding strategies for international wine manufacturers and distributors who wish to expand globally. In addition, there are managerial implications for domestic market where local retailers, merchandisers, importers can avoid importing products originating from offending countries and take on opportunity to exploit and promote “buy domestic campaigns”. Originality/value – Conceptually, this study extends the existing COO literature by (1) introducing bi-national brands into the model, (2) expanding on country of ownership appeals in evaluating bi-national brands and (3) identifying the correlation between the economic nationalism and consumer ethnocentrism constructs. Further, this research can significantly help wine marketers to develop more effective positioning strategies. It will also help in the development of pricing and promotional decisions.